1965
DOI: 10.1016/0014-4886(65)90059-2
|View full text |Cite
|
Sign up to set email alerts
|

The specific impedance of the dorsal columns of cat: An anisotropic medium

Abstract: Low frequency, nonstimulating current was passed from a small electrode on the surface of the dorsal columns in the cervical cord of cats. A glass microelectrode was used to record the voltage at distances of 0.5 to 2 mm from the current electrode. The voltage fell off more rapidly in depth and across the dorsal columns than it did longitudinally-the resistance was lower in the longitudinal direction. Accordingly, the dorsal columns are anisotropic. An approximate equation is presented which describes the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
1

Year Published

1967
1967
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(112 citation statements)
references
References 26 publications
5
106
1
Order By: Relevance
“…21 The worst case was a change in threshold stimulus of only 19% for DC ®bres and 27% for dorsal root ®bres (EG Olde Engberink, WA Wesselink, J Holsheimer, unpublished results).…”
Section: Computer Models Of Scsmentioning
confidence: 97%
See 1 more Smart Citation
“…21 The worst case was a change in threshold stimulus of only 19% for DC ®bres and 27% for dorsal root ®bres (EG Olde Engberink, WA Wesselink, J Holsheimer, unpublished results).…”
Section: Computer Models Of Scsmentioning
confidence: 97%
“…In this frequency range the transverse and longitudinal conductivities of the DCs vary approximately 23% and 3.5%, respectively. 21 Electrode de®nition In all models electrode contacts are de®ned in the dorsal epidural space, generally next to the dura mater or CSF. Coburn and Sin 11,16,17 represented each cathode or anode by a constant current source (+1 mA) con®ned to a single node of the mesh.…”
Section: Computer Models Of Scsmentioning
confidence: 99%
“…Encapsulation tissue dimensions and material properties also vary among different studies [13], and there is wide variability in reported conductivity data for different biological tissues. Furthermore, many biological tissues, including brain tissue, are anisotropic [29]. Additionally, this model does not consider local tissue variations, nor does it include alternative return current paths caused by areas in the brain filled by cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…The brain was assumed to consist of isotropic tissue of conductivity 0.27 S/m [29]. The conductivity of cerebrospinal fluid was assumed to be 1.6 S/m assuming human body temperature of 37 • C [30].…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Since the nerve fibres are randomly oriented, the white matter has been considered to have an equivalent volume of 1/3 of fibres longitudinal to the current path and 2/3 transverse (Ranck, Jr., 1963). The conductivity of a bundle of parallel axons was measured in the two directions in-vivo in the dorsal column of cats between 5 Hz and 50 kHz (Ranck, Jr. and BEMENT, 1965). An averaged conductivity (1/3 longitudinal + 2/3 transverse) was calculated as representative of the white matter.…”
Section: White Mattermentioning
confidence: 99%